Wet Distiller’s Grains and Wet Corn Gluten with Dry-Rolled or Whole-Shelled Corn in High-Energy Limit-Fed Diets Do Not Affect Growing Cattle Performance - T. J. Spore; S. P. Montgomery; E. C Titgemeyer; G. A. Hanzlicek; Christopher Vahl; T. G. Nagaraja; W. R. Hollenbeck; R. N. Wahl; Dale Blasi (Kansas Agricultural Experiment Station Research Reports, 2018)
Objective:Compare wet distiller’s grains plus solubles and wet corn gluten feed with dry-rolled or whole-shelled corn in a novel programmed-feeding strategy being developed at the Kansas State University Beef Stocker Unit. Description:A total of 320 crossbred steers were used to determine the effects of two corn by-products and methods of corn processing, utilizing a high-energy limit-fed feeding strategy. The Bottom Line:Kansas producers have the option of feeding corn by-product and whether or not to process corn in a high-energy limit-fed feeding strategy without the risk of negatively affecting performance.
Keywords: Stocker cattle; limit-feeding; wet distillers grains; wet corn gluten feed